Penerapan Metode Pembelajaran Cooperative Integreted Reading and Composition untuk Meningkatkan Hasil Belajar Mata Pelajaran Pendidikan Agama Islam pada Siswa Kelas Viii Smp Negeri 1 Padang Tualang - Ahmad Darlis; Muhammad Supawi; Mawadattul Haniah (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2020)
Mawaddatul Haniah. Application of Cooperative Integrated Reading And Composition Learning Methods to Improve Learning Outcomes of Islamic Religious Education Subjects for Class VIII Students of SMP N 1 Padang Tualang.The background of this research is that based on the identification carried out by the researchers at the research location, namely: There is still a lack of learning outcomes, it is proven that there are many students of class VIII SMP Negeri 1 Padang Tualang whose scores are below the Minimum completeness criteria. The objectives of this research are: To find out how the students' learning methods in Islamic Religious Education (PAI) class VIII SMP N 1 Padang Tualang before and after using the cooperative integrated reading and composition learning method. This research was conducted in the form of classroom action research. According to the type of research chosen, namely classroom action research, this research uses an action research model in the form of a spiral and from one cycle to the next. The results of this study are: Student learning outcomes in the subject of Islamic Religious Education class VIII SMP Negeri 1 Padang Tualang after using the Cooperative Integrated Reading And Composition learning model have increased, In the analysis of the test results of cycles I and II it can be seen that there is an increase in learning outcomes students, namely in cycle one students who have a complete score of only 20 students or 80% and in the second cycle students who complete 100%. .